CRITICAL REVIEW: EFEK DARI HETEROGENITAS BOARD CAPITAL TERHADAP STRATEGIC CHANGE - Jean Richard Jokhu (FIRM Journal of Management Studies, 2019)
Many board of directors research was dominated by director diversification. In this study the researcher try to explore Hayman and Hilman (2010) research that enforce board of directors diversification as on of competitive advantage of the firm that strengten firm performance. Using strategic management lenses we provide new perspective and also adding change management as one of the outcome of direction diversification.